Viscoelastically prestressed polymeric matrix composites – Effects of delayed moulding on Charpy impact properties. (June 2019) - Qin, Yang; Fancey, Kevin S.
Abstract: Viscoelastically prestressed polymeric matrix composites (VPPMCs) are produced by subjecting fibres to creep, then releasing the creep load before moulding. Previous work has demonstrated mechanical property improvements up to ∼50% from nylon 6, 6 fibre-polyester resin VPPMCs, compared with control (unstressed) counterparts. Since fibre stretching and moulding processes are decoupled, the time interval between releasing the fibre stretching load and moulding (delayed moulding) offers considerable production flexibility. This paper investigates delayed moulding over 0–1272 h, using fibres stored at 20 °C and −25.4 °C. Charpy impact tests demonstrated increased energy absorption from all VPPMC samples compared with control counterparts, this increase reducing with delayed moulding time. A 1272 h delay gave an increase of ∼23% for fibre storage at 20 °C, and ∼40% at −25.4 °C, the latter demonstrating "decelerated" ageing. For all samples, the magnitude of fibre-matrix debonding (the principal energy absorption mechanism) increased linearly with impact energy data.